Bandwidth and Gain Enhancement of Microstrip Leaky-Wave Antennas with Slot and Defected Ground Structure - Fitri Yuli Zulkifli; Muhamad Wahyu Iqbal (Directorate for Research and Community Services, Institut Teknologi Bandung, 2023)
This paper discusses the design, simulation, and realization of a leaky-wave microstrip antenna with multiple slots and defected ground structure (DGS). The leaky-wave microstrip antenna with multiple slots and DGS was designed to operate at 5.925-6,425 GHz for wireless local area network applications (WLANs), with a gain of ≥4dBi. The antenna uses FR-4 epoxy as the substrate with a dielectric constant of 4.6 and a thickness of 1.6 mm. The leaky-wave microstrip antenna has dimensions of 45.1 mm × 24.8 mm × 1.6 mm, while the leaky-wave microstrip antenna with multiple slots and DGS has dimensions of 40.6 mm × 25 mm × 1.6 mm. The simulation results showed that adding multiple slots and DGS to the leaky-wave microstrip antenna increased the bandwidth from 280 MHz (5.859–6.139 GHz) to 691 MHz (5.854–6.545 GHz) while the gain increased from 4.47 to 5.04 dBi. Meanwhile, the measurement results showed that the bandwidth parameter increased from 273 MHz (5.877–6.150 GHz) to 684 MHz (5.845–6.529 GHz) and the gain parameter from 4.53 to 5.06 dBi at 6 GHz.